Energy saving monitoring using fuzzy logic for computing lab - Tariq, Fareeha; Abdullah, Lili Marziana; Sulaiman, Suriani; Tariq, Waqar (World Academy of Research in Science and Engineering, 2019)
The important issue for societies, enterprises and governments is to improve energy efficiency and reduce energy demand consumed by large number of computers and servers that could have an extensive impact on the environment. ICT creates many environmental issues such as high consumption of electrical energy from large number of computers and other I.T equipment’s. I.T industry has invented that Green Information Communication Technology (GICT) is a good way to treat with the major environmental and energy related problems faced by every country because it improves overall energy productivity while also maintaining the healthy energy consumption. In this paper, a brief overview on Green ICT implementation in IIUM computer lab by the help of energy audit in ICT lab, survey questionnaires and interview sessions. The paper will contribute by presenting the prototype which is based on energy saving monitoring by using Fuzzy Logic algorithm. Moreover, in this paper we will also giving our recommendations on Green ICT practices.